Pemetaan Sistematik Publikasi Penelitian Pustakawan Data Mengunakan Scientopy - Nur Rizzal Rosiyan (Media Pustakawan, 2023)
Data librarians are librarians who work in libraries assisting users as Data Management Consultant, Data Mining Consultant, Data Research Scientist, Data Services Librarian, Design Data Librarian, Digital Archivist, Digital Collections, Strategist and Architecture Librarian, Digital Humanities Design Consultant, Digital Records Archivist Manager, Data Management Services, Research Data Librarian, Research Data Management Coordinator, Scientific Data Curation, Specialist/Metadata Librarian, Scientific Data Curator, Social Science Data Consultant. This study aims to determine the distribution of data librarian research publications by year, the most productive researchers publishing data librarian research, the most productive publishers publishing data librarianship, the distribution of data librarian research by country, the distribution of data librarian research by document type, and the distribution of data librarian research by subject. The study was conducted using a scientometric approach using the open source software Scientopy. Data collection was carried out by searching using the keywords data librarian and data librarianship. Data collection was carried out on October 13, 2023, and 857 documents were obtained. The results of the analysis show that the systematic mapping of data librarianship research publications has been carried out since 2006, and the peak occurred in 2023. The most productive researchers in publications with 5 documents and the number of h-index 4, with the most published document type in the form of articles as many as 480 documents The most common subject is information science and library science, with 149. The country with the most productivity is the United States, with the highest citation rate of 33.